Genetic expression signatures of oral submucous fibrosis and oral cancer-A preliminary microarray report - Pao-Hsin Liao; Hui-Wen Yang; Yu-Feng Huang (Elsevier, 2016)
Background/purpose: Oral submucous fibrosis (OSF) is a potentially malignant disorder of oral squamous cell carcinoma (SCC). In this study, we obtained the genetic expression signatures of OSF and SCC by microarray analysis. Materials and methods: Five patients with clinically evident OSF, five patients with SCC who also had existing OSF, and four normal volunteers who did not have a history of chewing betel quids were recruited. Biopsy specimens were obtained with an approved Institutional Review Board protocol. Total RNA from OSF or SCC was isolated and hybridized to a Human Oligo 1A (V2) Microarray (G4110B) chip against normal control RNA that was pooled from the four healthy volunteers. Results: We found similar, but distinct genetic expression signatures for OSF and SCC. At the hierarchical clustering analysis, 24 known genes (23 upregulated and 1 downregulated) in OSF were differentially expressed consistently in all participants. Among the genes, XRCC5 was cloned and transfected into oral cancer GNM cells. The results demonstrated that the overexpression of XRCC5 increased the resistance of GNM cells to low-density X-ray irradiation and promoted the cell growth rate. Conclusion: The distinct but similar genetic expression signatures seen in OSF and SCC suggested that this expression may be used as a supplemental diagnostic tool in pathology practice. This preliminary study showed that the XRCC5 gene promoted GNM cell growth and conferred resistance to low-density X-ray irradiation. Further studies on the effect of XRCC5 in oral cancer cells are in progress.